Gender-Based Violence from Scientific Evidence: Systematic Review of Studies Published between 2020 and 2024 - Barrós Cordero, Diurey (2026)
This research was conducted through a systematic analysis of the scientific literature on gender-based violence, between the years 2020 and 2024, extracted from databases such as Scopus, Web of Science, and SciELO, under language and thematic relevance criteria. The design is narrative, with a qualitative approach. This process allowed for the identification and selection of 25 qualitative studies that met the established criteria, all of which are relevant to the topic with the purpose of examining the extent to which this phenomenon has been addressed from a global perspective. Theories such as gender-based violence against women and prejudice-based violence are presented. Additionally, a theoretical approach was developed on its different modalities, including school bullying, domestic violence, physical, psychological, sexual violence, violence in armed conflict situations, cyberbullying, among others. The conclusions proposed theoretical foundations for each modality of gender-based violence, representing a valuable contribution for future studies. It is emphasized that the theories should be interpreted considering the specific dynamics of this phenomenon, taking into account the diversity of criteria.